The Effect of Subconjunctival Ranibizumab on Corneal and Anterior Segment Neovascularization: Study on an Animal Model. Issue 3 (May 2014) - Liarakos, Vasilios S.; Papaconstantinou, Dimitrios; Vergados, Ioannis; Douvali, Maria; Theodossiadis, Panagiotis G.
Purpose: To evaluate the effect of subconjunctival anti—vascular endothelial growth factor (VEGF) ranibizumab on corneal and anterior segment neovascularization. Methods: In this experimental study and laboratory investigation, chemical cauterization was utilized to induce corneal neovascularization in 16 rabbits randomly divided in 2 equal groups. Cauterized eyes were either treated with 0.1 mL (1 mg) of subconjunctival ranibizumab or administered a sham injection. A third group of 4 rabbits served as control for side effects after ranibizumab administration. All animals were monitored daily for 14 days and the extent of corneal scarring and neovascularization was measured on days 1, 7, and 14. After enucleation, ocular tissues were separated under a surgical microscope and VEGF levels were measured with ELISA. Statistical analysis was performed to compare the extent of corneal neovascularization and VEGF levels between treated and untreated eyes. Results: Subconjunctival ranibizumab inhibited corneal neovascularization significantly both in the first and the second week compared to untreated controls (p = 0.006 and p = 0.001, respectively). The VEGF levels were significantly lower in all anterior segment tissues like the cornea, iris, aqueous humor, and conjunctiva of the treated eyes (p<0.01). The reduction of VEGF levels ranged from 19% to 73% in different ocular tissues. Corneal scarring was not significantly affected by anti-VEGF treatment (p = 0.7). No side effects were noticed. Conclusions: Early subconjunctival administration of ranibizumab may successfully inhibit alkali-induced corneal neovascularization in an animal model. Subconjunctival ranibizumab reduces VEGF levels significantly not only in the cornea and the bulbar conjunctiva but also in the aqueous humor and the iris.